Pola Komunikasi Interpersonal Orang Tua terhadap Perkembangan Kognitif Anak Usia Dini - Sylvi; Santi Indra Astuti (UNISBA Press, 2024)
Abstract. This study aims to determine the pattern of interpersonal communication between parents and early childhood in Cimenyan State Kindergarten in supporting cognitive development. Children at an early age level (kindergarten) need guidance to help physical and spiritual growth and development so that children have the preparation to enter primary school. The discussion of this research focuses on parents' interpersonal communication patterns on cognitive development of early childhood, therefore researchers want to know more deeply about how parents' interpersonal communication patterns on children's cognitive development (kindergarten) with aspects of communication patterns. This study uses qualitative research methods, with data collection techniques of interviews and observations to parents, teachers and students of Cimenyan State Kindergarten as research subjects. Data were analyzed using data reduction analysis techniques, data presentation and conclusion drawing, as well as triangulation for data validity. The results of the study Interpersonal communication that exists between parents and early childhood at TK Negeri Cimenyan is going well, but parents as the main educators and those who have the most time with children are still not aware of factors that can hinder communication and child development. Abstrak. Penelitian ini bertujuan untuk mengetahui pola komunikasi interpersonal antara orang tua dan anak usia dini di TK Negeri Cimenyan dalam menunjang perkembangan kognitif. Anak pada jenjang usia dini (TK) memerlukan pembinaan untuk membantu pertumbuhan dan perkembangan jasmani dan rohani agar anak memiliki persiapan untuk memasuki sekolah dasar. Pembahasan penelitian ini berfokus pada pola komunikasi interpersonal orang tua terhadap perkembangan kognitif anak usia dini, maka dari itu peneliti ingin mengetahui lebih dalam lagi mengenai bagaimana pola komunikasi interpersonal orang tua terhadap perkembangan kognitif anak (TK) dengan aspek-aspek pola komunikasi. Penelitian ini menggunakan metode penelitian kualitatif, dengan Teknik pengumpulan data wawancara dan observasi kepada orang tua, guru dan siswa TK Negeri Cimenyan sebagai subjek penelitian. Data dianalisa dengan menggunakan Teknik analisis reduksi data, penyajian data dan penarikan kesimpulan, serta triangulasi untuk keabsahan data. Hasil dari penelitian Komunikasi interpersonal yang terjalin antara orang tua dan anak usia dini TK Negeri Cimenyan berjalan dengan baik namun orang tua sebagai pendidik utama dan pihak yang paling banyak memiliki waktu bersama anak masih belum menyadari faktor yang dapat menghambat komunikasi dan perkembangan anak.